Sustainable Tourism in Banyumas Regency Based on Local Wisdom After the COVID-19 Pandemic - Yamin, Muhammad; Arya Aditia Utama, I Putu; Sahat Satyawan, Darmanto (KnE Social Sciences, 2023)
Banyumas is a regency in Central Java, Indonesia. Its location, which is between Mount Slamet and the Serayu River, gives this area the potential for natural beauty for tourism. Its natural beauty has become a tourist attraction in the natural tourism sector. This research is important to see the threat of environmental damage and sustainability caused by natural tourism. Therefore, this study uses the concept of sustainable tourism as an analytical tool to see the policies taken in order to improve the tourism sector by minimizing environmental damage due to tourism in Banyumas Regency. The conceptualization of sustainable tourism in Banyumas is seen from three main factors, environmental, economic, and socio-cultural. Qualitative descriptive methods were used in this study with data collected from research results, journal articles, and secondary data as a reference. An important finding in this study is that socio-cultural factors that are implemented in the form of local wisdom are key factors for the Banyumas community in realizing sustainable tourism. Keywords: Banyumas Regency, Sustainable Tourism, Local Culture